Rui Moreira and the 2013 local elections: the media visibility of an independent candidate - Resende, Filipe (2016)
This article focuses on the Rui Moreira’s visibility as political and media construction in 2013 municipal elections. Therefore, the theoretical component focuses on political mediatization and political celebrity concepts. This definition is possible due to the approximation between media and politics. The union developed a popularization in public communication. Therefore, many public figures had applied for different elections. This research focuses on the quantitative study with content analysis. Thus, the main objectives are the research of the media coverage of Rui Moreira, specifically of his activities in media and his journalistic coverage. Our research suggests that this independent candidate is a political celebrity result of popularity. The status attained by Rui Moreira was also constructed by a positive media framing of this personality in the public space.